Diagnostic Accuracy Of Different Clinicopathological Parameters In The Differentiation Of Septic Versus Aseptic Mono-Arthritis In The Paediatric Age Group - Hussain, Warda; Waqas Ali; Akhtar, Rahman Rasool; Gul, Naveed; Pasha, Waseem; Siddiq, Muhammad Zahid (Journal of Rawalpindi Medical College, 2025)
Objective: Determining the diagnostic accuracy of various clinicopathological parameters in differentiating Septic Arthritis versus Aseptic Inflammatory Arthritis in the paediatric age group. Methods: A cross-sectional study took place at the Department of Orthopedics, Nawaz Sharif Medical College, University of Gujrat, Gujrat, from February 2023 to July 2024. 150 children aged 10-160 months, of either gender, presented for the first episode of acute monoarthritis lasting for less than a week were included and categorized into two groups. Group A included children with confirmed diagnosis of SA and Group B included children diagnosed with aseptic inflammatory arthritis. Body temperature and serum inflammatory markers were measured. Receiver operating characteristic curves were made to discover the optimum diagnostic cut-off values of the parameters. The areas under the curves were then estimated to juxtapose the overall predictive accuracy for SA. Results: 49.33% of patients had SA and 50.67% had Aseptic Inflammatory Arthritis. All clinicopathological parameters including body temperature, TLC, ANC, NP, ESR, and CRP exhibited significantly higher values in Group A than in Group B (p<0.01). TLC had a considerable discriminatory power in distinguishing SA from aseptic inflammatory arthritis followed by ESR, CRP, NP, body temperature and ANC. Conclusion: In conclusion, these clinicopathological parameters can be used for the prompt diagnosis of SA to start the treatment and prevent the progression of the disease.